Intervention with α-Ketoglutarate Ameliorates Colitis-Related Colorectal Carcinoma via Modulation of the Gut Microbiome. (17th June 2019) - Li, Si; Fu, Chenxing; Zhao, Yurong; He, Jianhua
Abstract : The intestinal microbiome plays a crucial role in promoting intestinal health, and perturbations to its constitution may result in chronic intestinal inflammation and lead to colorectal cancer (CRC). α -Ketoglutarate is an important intermediary in the NF- κ B-mediated inflammatory pathway that maintains intestinal homeostasis and prevents initiation of intestinal inflammation, a known precursor to carcinoma development. The objective of this study was to assess the potential protective effects of α -ketoglutarate intervention against CRC development, which may arise due to its known anti-inflammatory and antitumour effects. CRC was induced in C57BL/6 mice using azoxymethane (AOM) and dextran sulfate sodium (DSS). Tumour frequency, histological rating, and colonic microbiota were assessed in colonic samples. The findings demonstrated that α -ketoglutarate offered significant protection against CRC development in mice. Furthermore, α -ketoglutarate also exhibited immunomodulatory effects mediated via downregulation of interleukin (IL)-6, IL-22, tumour necrosis factor (TNF)- α, and IL-1 β cytokines. Finally, intervention with α -ketoglutarate tended to minimise the frequency of opportunistic pathogens ( Escherichia and Enterococcus ) while increasing the populations of Akkermansia, Butyricicoccus, Clostridium, and Ruminococcus . Taken together, our findings show that dietary α -ketoglutarate intervention may protect against inflammation-related CRC.